2003
DOI: 10.1016/s0035-9203(03)80038-x
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate plus sulfadoxine-pyrimethamine for uncomplicated malaria in Kenyan children: A randomized, double-blind, placebo-controlled trial

Abstract: Plasmodium falciparum has developed resistance to almost all routinely used antimalarial drugs. Sulfadoxine-pyrimethamine (SP) has replaced chloroquine as first-line treatment of uncomplicated malaria infection in Kenya but resistance to SP is already reported. The addition of artemisinin derivatives to SP may delay the development of drug resistance, improve cure rates, and reduce transmission. The efficacy and safety of artesunate plus SP in the treatment of uncomplicated P. falciparum malaria was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…Hundred percent efficacy of AS plus SP was recently reported from eastern Sudan [8] and 99% from southern Sudan [12]. The high cure rate in this study is comparable to that reported from neighbouring African countries [5,6]. However, the highest drug resistant P. falciparum strains were reported from eastern Sudan [11,16].…”
Section: Discussionsupporting
confidence: 78%
“…Hundred percent efficacy of AS plus SP was recently reported from eastern Sudan [8] and 99% from southern Sudan [12]. The high cure rate in this study is comparable to that reported from neighbouring African countries [5,6]. However, the highest drug resistant P. falciparum strains were reported from eastern Sudan [11,16].…”
Section: Discussionsupporting
confidence: 78%
“…Children with a high prevalence of malaria-associated anaemia, arising probably from chronic asymptomatic parasitaemia, may need repeated doses of an effective antimalarial therapy, combined with vector control. The efficacy of an ACT depends strongly on the efficacy of the partner drug used with the artemisinin derivative Obonyo et al, 2003). In the present study, it was almost certainly the high prevalence of SP resistance that compromised the efficacy of the AS1 and AS3 combinations, in terms of both parasitological cure and haematological recovery.…”
Section: Discussionmentioning
confidence: 64%
“…Drawing from the standard health facility formulary, the health worker had the option of providing quinine, which is bitter and can be difficult to administer for the full seven-day treatment regimen, sulfadoxine-pyrimethamine, which is well tolerated and easily administered, but has poor treatment efficacy in Kenya because of high levels of resistance, 24 or a prescription, which may not be filled as prescribed in this rural setting with few licensed pharmacies, and an impoverished population. Thus, the increase in malaria-specific mortality may have been caused by lack of access to any effective antimalarial drug during times of AL stock-out.…”
Section: Antimalarial Drug Stock-outs After Its Introduction Inmentioning
confidence: 99%